A Three-Dimensional Simulation of Supercell Convective Storm - V. Spiridonov; Z. Dimitrovski; M. Curic (Advances in Meteorology)
A supercell convective storm is simulated by using a cloud-resolving model. Numerical experiments have been performed in 3D by using the same domain size, with a different spatial and temporal resolution of the model. High-resolution cloud model has been shown to represent convective processing quite well. Running the model in a high-resolution mode gives a more realistic view of the life cycle of convective storm, internal structure, and storm behavior. The storm structure and evolutionary properties are evaluated by comparing the modeled radar reflectivity to the observed radar reflectivity. The comparative analysis between physical parameters shows good agreement among both model runs and compares well with observations, especially using a fine spatial resolution. The lack of measurements of these species in the convective outflow region does not allow us to evaluate the model results with observations. A three-dimensional simulation using higher grid resolution mode exhibits interesting features which include a double vortex circulation, cell splitting, and secondary cell formation.